New Approach: Induction Heat Treatment of Large Diameter Pipes and Coils - V. Demidovich; Yu. Perevalov (Advanced Aspects of Engineering Research Vol. 4, 2021)
New approach of designing and control of induction heat treatment installations with utilizing of numerical models is developed. Models include two-dimensional simulation of coupling electromagnetic and temperature fields in cylindrical systems for processing of pipes and rolls. Also, thermal and structural tension during heating and cooling of pipes and rolls are simulated. These data allow defining structure, hardness, the size of grain and other properties of the pipes and rolls. They allow optimizing design and a choice of equipment, a heat treatment mode for achievement of the maximum quality and minimization of energy consumption. The developed models were used not only for the design of induction heat treatment systems of pipes and rolls, but also for a digital control of these complexes. New technologies for induction heat treatment of large diameter pipes (40”– 62”) and rolls of rolling mills with a barrel diameter of up to 65” are developed. Developed computer control systems use specialized numerical models that provide high quality heat treatment and minimize residual stresses.